Age Friendly Transport for Greater Manchester - Charles Musselwhite (2018)
Background and MethodologyMobility and travel is important to older people, reduced mobility is linked to poorer mental and physical health for a variety of reasons. There is a decline in driving in later life and walking and using public buses are common modes of transport for older people throughout the Greater Manchester (GM) area. GM has a higher than average amount of deprivation and healthy life expectancy is lower than the English average. Keeping people active and mobile from a younger age, especially through walking, cycling or using the bus, can reduce the impact of this inequality in later life. Workshops were set up in six different locations in GM (Tameside, Bolton, Bury, Oldham, Wigan, Salford) with older people and advocates. Each workshop got participants to identify and prioritise key issues they have with transport and mobility, followed by discussions on solutions to these issues. Issues with transport identified Walking1.Poor quality pavements. – poor upkeep and maintenance were noted with a risk of falls.2.Obstructions on pavements – including parked cars, cyclists and mobility scooters.3.Pedestrian crossings – length of time given to cross was seen as too short and crossings often placed in wrong place with a lack of dropped kerbs and issues with blistered paving.4.Speeding traffic near to pedestrian area – making it unpleasant, dangerous and difficult to cross 5.Lack of benches and toilets6.Poor street lighting (especially an issue in Wigan)7.Pollution (especially an issue in Wigan)Cycling It would help cyclists and also pedestrian and drivers if dedicated cycle paths were built.Public Buses1.Bus driver awareness of older people’s issues – especially drivers driving off before the person had sat down, not being sympathetic to older people struggling with their pass or with bags and not stopping close enough to the kerb for people to easily board and alight. 2.Poor bus service - including the bus stop being poorly cited not close to residential areas (esp Wigan and Oldham) or the bottom of hills (esp Wigan) and unreliability of service (esp. Oldham) and difficulty swapping between buses with different operators (all areas). 3.Poor bus stops – poor signage and information (esp. Oldham and Bolton) and lack of seating.4.Poor quality buses – Drop down mechanisms that fail and lack of grab rails on the bus.5.Extending free bus pass to before 9:30am - especially for hospital and doctor appointments.Community transport and ring and ride services There was some ambiguity over who was eligible to use community transport. Some people even discussed not knowing community transport existed at all. Second, some felt the service was too inconvenient and unreliable, taking too long to travel to places. Railway serviceHighest priority area was lack of help, tickets being confusing and not getting a seat. More minor priorities were accessibility at railway stations and cleanliness of trains. Driving Difficulty getting a blue disabled badge if needed on a temporary basis was noted. Lack of drop off points near health centres and bus stops was also discussed. Finally cars parked on the road and on pavements can be an issue to drivers. PolicyNot being involved in decisions affecting transport was frequently noted. Coupled with this was feeding back, including lack of confidence in reporting and time taken to make any changes. Underinvestment in areas outside of London was a very common and very important issue. SolutionsThe participants ranked the solutions around priority and how long it would take to implement. Priority areas are those that older people felt need to be done first and would have highest effect included: training for frontline public transport staff, concessionary bus pass to operate before 9:30, developing Transport Action Group, implementing a community toilet scheme and take a seat campaign and having audio-visual bus stops. There were then two groups where a strategy would be needed in order to reach the goal and where a slightly longer term plan would be required, these included auditing local areas, reforming local bus services, general pavement improvements, bus buddy scheme, Independent Transport Networks and low emission plans. Information sharing website.Recommendations Recommendations based on these were developed in five key areas•Recommendation 1: Staff working in transport to be trained in older people’s issues•Recommendation 2: Getting more older people involved in transport planning and design•Recommendation 3: That other sectors help manage transport demand better•Recommendation 4: Community resources and support•Recommendation 5: Demonstrator communities